PEMANFAATAN MEDIA AUDIOVISUAL UNTUK MENINGKATKAN PEMAHAMAN KONSEP LARI ESTAFET PADA SISWA SEKOLAH DASAR - Alim, Bahrul; Butsiarah, Butsiarah; Saiful Alimsyah, Andi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to describe how audiovisual media were utilized to improve elementary school students’ understanding of relay running concepts at SD Negeri 7 Salotungo. The study employed a descriptive qualitative design with a case-study orientation. Data were collected through learning observations, informal interviews with the physical education teacher, and documentation of classroom and field activities. The learning sequence consisted of presenting short audiovisual clips, guided questioning, and immediate relay practice in the school yard. Data were analyzed through reduction, display, and conclusion drawing, while trustworthiness was strengthened through source and technique triangulation. The findings show that audiovisual media helped students understand the sequence of runners, the exchange zone, baton passing techniques, movement timing, and teamwork more concretely. Students demonstrated higher attention during lesson presentation, participated more actively in discussion, and moved to field practice with better readiness and confidence. The combination of video, teacher scaffolding, and contextual practice reduced misconceptions that commonly emerge when relay running is taught only through verbal explanation. The study concludes that audiovisual media function effectively as pedagogical support in elementary physical education when the videos are short, focused, and directly linked to guided practice